PENGGUNAAN MOBILE APPS “OUR MODERATE GAME” MEDIA EDUKASI PENINGKATAN TOLERANSI TINJAUAN FILSAFAT ILMU - ilham, Iing; Ramadani, Zahrotun Nurur (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2024)
Our Moderate Game (OMG) is an innovative application that integrates game elements with multicultural education objectives to increase tolerance among users, especially teenagers. In the era of technology 5.0, where the development of AI, IoT, and robot technology is in focus, OMG answers these challenges by providing tolerance education through game simulations. This application uses a qualitative method with a case study approach to understand the impact of using OMG on teenagers. Through features such as shop, book, play, and religious information, OMG creates a comprehensive learning experience. The shop feature provides incentives for players to understand and apply the value of tolerance, while the book feature provides in-depth information and detailed explanations. The games in OMG provide interactive experiences, build player character, and offer a sense of achievement. In addition, the religious information feature helps players understand the diversity of religions in Indonesia, increasing tolerance towards others' beliefs. By combining engaging game elements with educational objectives, OMG succeeds in creating an entertaining and educational learning environment. This application is not just entertainment, but also an effective tool in shaping positive attitudes towards differences and maintaining Indonesia's diversity.